1992
DOI: 10.1021/ic00032a022
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of KxMIIxMIII1-xF3 (x .apprxeq. 0.4-0.6; MII = manganese, nickel; MIII = vanadium, chromium)

Abstract: The compounds K,M11xM1111-xF3 ( x = 0.4-0.6; M" = Mn, Ni; MI1' = V, Cr) were prepared and studied. The tetragonal tungsten bronze structure formed for M" = Mn and M"' = V, Cr, and the modified pyrochlore structure formed for MI1 = Ni and M111 = V, Cr, except for &.soNio.soCro.MF3, which formed the tetragonal bronze structure. From their magnetic behavior, we conclude that all of the tetragonal bronze compounds are ionically ordered and belong to space group P4gc (Ck). Magnetic ordering in these compounds occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…Ferroelasticity and ferroelectricity are coupled at temperature lower than T c = 490 K. In addition, a spontaneous ferromagnetic component appears below 120 K, in the magnetically ordered phase [13,45,46].…”
Section: Ferromagnetismmentioning
confidence: 99%
“…Ferroelasticity and ferroelectricity are coupled at temperature lower than T c = 490 K. In addition, a spontaneous ferromagnetic component appears below 120 K, in the magnetically ordered phase [13,45,46].…”
Section: Ferromagnetismmentioning
confidence: 99%
“…First, the linear trimers would all have nearest-neighboring M 2 + ions along the c direction. Secondly, the fluoride analogs of TTB seldom form over the entire range of x (0.40-0.60) [3]. The composition closest to ideal is K 0:50 M II 0:5 M III 0:5 F 3 ( ¼KM II M III F 6 ) (Fig.…”
Section: Introductionmentioning
confidence: 98%
“…This M 2 + -M 3 + -M 2 + -M 3 + ordering assures that M 2 + ions have only M 3 + ions for nearest neighbors along the c axis, and vice versa. Hong et al [3] concluded that M 2 + -M 3 + ionic ordering (as illustrated in Fig. 1b) is common in first row transition metal fluorides having the TTB structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations